Computer science approach to quantum control (2019)
These works considers several hypothetical control processes on the nanoscopic level and show their analogy to computation processes. It shows that measuring certain types of quantum necessarily be an extremely powerful computer.observables is such a complex task that every instrument that is able to perform it would